2016
DOI: 10.1186/s13063-016-1673-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the WHO Safe Childbirth Checklist program in reducing severe maternal, fetal, and newborn harm in Uttar Pradesh, India: study protocol for a matched-pair, cluster-randomized controlled trial

Abstract: BackgroundEffective, scalable strategies to improve maternal, fetal, and newborn health and reduce preventable morbidity and mortality are urgently needed in low- and middle-income countries. Building on the successes of previous checklist-based programs, the World Health Organization (WHO) and partners led the development of the Safe Childbirth Checklist (SCC), a 28-item list of evidence-based practices linked with improved maternal and newborn outcomes. Pilot-testing of the Checklist in Southern India demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 26 publications
0
51
0
1
Order By: Relevance
“…The methodology of the trial is available elsewhere, 20 and a detailed description of the intervention is published as a companion article in this issue of Global Health: Science and Practice 21 . Impact results on perinatal mortality, maternal mortality, and severe maternal morbidity will be reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methodology of the trial is available elsewhere, 20 and a detailed description of the intervention is published as a companion article in this issue of Global Health: Science and Practice 21 . Impact results on perinatal mortality, maternal mortality, and severe maternal morbidity will be reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…To support ongoing facility-level adherence to essential practices, a facility staff member was identified and trained to support SCC use after the intervention was completed. The program is described in more detail elsewhere 18 , 20 , 21 . Technical training and supplies were not provided.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the WHO developed the Safe Childbirth Checklist which includes 29 EBPs that focus on maternal and neonatal outcomes at four pause points – on admission to the facility, at the time of pushing (or before cesarean delivery), soon after birth (within 1 h) and at discharge. This checklist has been used in a variety of LMICs contexts, including India, Sri Lanka, and Namibia [911]. In Namibia, the authors reported an increase of EBPs from 68% to 95% over a 6-month period, as well as a reduction in perinatal mortality from 22 to 13.8 deaths/1000 deliveries [11].…”
Section: Introductionmentioning
confidence: 99%